Memetic algorithm to minimize costs of activities in rcpsp (2012)
The Resource-Constrained Project Scheduling Problem (RCPSP) is a classic and important problem in project management and has got much attention from researchers. In this paper, we consider the case in which the cost of activities has to be minimized. This variant of the problem can be found mainly in construction management supply chains. Its characteristics show that this objective function is non-regular and that the problem is NP-hard. This paper presents a memetic algorithm to solve this problem. Computational experiments are carried out using well-known instances from the PSPLIB. Results obtained validate the effectiveness of the proposed algorithm and allow us to understand the algorithm’s behavior